2023
DOI: 10.3390/cimb45040198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella sativa on Selected Gastrointestinal Diseases

Abstract: Nigella sativa L. (family Ranunculaceae), also known as black cumin, has been used in cuisine around the world for many years. Due to its health-promoting properties, it can be used not only in the food industry but also in medicine. The main bioactive compound contained in the black cumin extract is thymoquinone (TQ), which has a special therapeutic role. The results of research in recent years confirmed its hypoglycemic, hypolipemic, and hepatoprotective effects, among others. In addition, the results of lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 105 publications
0
1
0
Order By: Relevance
“…Biologically active compounds from Nigella sativa have been shown to have antioxidant, antimicrobial, antiinflammatory, antidiabetic, hepatoprotective, antiproliferative, proapoptotic, antiepileptic and immunomodulatory activities, among others [48][49][50][51][52][53][54]. Black seed could also be used for the prevention of some diseases, such as cardiovascular disease, diabetes, gastrointestinal diseases or wound healing [20,[55][56][57][58][59]. In clinical studies, Nigella sativa and its constituents, including TQ, have demonstrated antimicrobial, antioxidant, anti-inflammatory, anticancer and anti-diabetic properties, as well as therapeutic effects on metabolic syndrome and gastrointestinal, neural, cardiovascular, respiratory, urinary and reproductive disorders [54].…”
Section: Preclinical and Clinical Studies On Thymoquinone And Its Mai...mentioning
confidence: 99%
“…Biologically active compounds from Nigella sativa have been shown to have antioxidant, antimicrobial, antiinflammatory, antidiabetic, hepatoprotective, antiproliferative, proapoptotic, antiepileptic and immunomodulatory activities, among others [48][49][50][51][52][53][54]. Black seed could also be used for the prevention of some diseases, such as cardiovascular disease, diabetes, gastrointestinal diseases or wound healing [20,[55][56][57][58][59]. In clinical studies, Nigella sativa and its constituents, including TQ, have demonstrated antimicrobial, antioxidant, anti-inflammatory, anticancer and anti-diabetic properties, as well as therapeutic effects on metabolic syndrome and gastrointestinal, neural, cardiovascular, respiratory, urinary and reproductive disorders [54].…”
Section: Preclinical and Clinical Studies On Thymoquinone And Its Mai...mentioning
confidence: 99%
“…In light of this, several reports revealed that black seed oil (BSO) has a p healing effect on gastric ulcers [14,15]. Along with this, various studies sho administration of thymoquinone (TMQ), the major constituent in BSO, reduc cers produced by NSAIDs and other agents like ethanol [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating this plant compound into the diet can be an effective prophylactic and therapeutic measure. However, its potential interactions with drugs that are used to treat chronic diseases must be monitored [18].…”
mentioning
confidence: 99%